Hériter au Canada : portrait des tendances entre 2005 et 2019 - Camille Biron-Boileau (Enfances, Familles, Générations)
Research Framework: The growing contribution of inheritance to social inequality in many countries is stimulating research into how this transmission takes place within families. However, very few studies have been conducted on the subject in the Canadian context.Objectives: This research examines the extent to which Canadian families benefit from inheritance according to their social position. It also aims to study the temporal trends specific to the phenomenon, as well as the factors explaining the changes observed. Methodology: Using 2005, 2012, 2016, and 2019 data from the Survey of Financial Security, regressions were conducted to study the odds of receiving an inheritance, and its value according to household characteristics and survey year.Results: Families with higher socioeconomic status are more likely to receive an inheritance, generally of greater value. A rise in inheritance has also been observed in Canada. Changes in the age structure partly explain this, but the more significant increase observed in Quebec and among households of lower socioeconomic status indicates the influence of other factors. Conclusions: Inheritance contributes to the reproduction of economic inequalities due to its unequal distribution, and is a growing factor in Canada. The aging population explains some of the trend, but the influence of increasing rates of home ownership and house prices, as well as a change in wealth accumulation behaviours for children, may also be at play. Contribution: This article contributes to the understanding of inheritance, which has scarcely been studied in Canada. The unequal distribution of inheritance raises equality issues in opportunity, and the role of the state in mitigating its effects.